Bolonjski proces in slovenske visokošolske knjižnice - Ivančič, Jerneja (Knjižnica, 2004)
The article briefly describes the Slovenian higher education arena and also academic libraries as an important part of the higher education system. Furthermore, the Bologna Process is described, its beginnings and its goals, but especially the impact on the Slovenian higher education arena and on academic libraries as well. The later could make numerous improvements in their work activities and in quality contribute to the realization of the "Bologna ideas".
Keywords: bolonjski proces; visokošolske knjižnice; visoko šolstvo; Slovenia; Slovenija